Topical Application of 7,3′,4′-Trihydroxyisoflavone Alleviates Atopic Dermatitis-Like Symptoms in NC/Nga Mice - Park, Sang Hun; Lee, Chang Hyung; Lee, Ji Yun; Yang, Hee; Kim, Jong Hun; Park, Jung Han Yoon; Kim, Jong-Eun; Lee, Ki Won (Planta Medica, 2020)
Atopic dermatitis is a skin disease characterized by chronic inflammatory lesions, and new therapies are needed to address its rising prevalence. Soy isoflavone has been highlighted as a potential new cosmeceutical material that may have applications in atopic dermatitis care. We have developed a technique to attach an additional -OH group to the ortho position of -OH in the phenol ring using a special enzyme. By adding the -OH group to daidzein, 7,3′,4′-trihydroxyisoflavone can be generated for possible use as a cosmeceutical and functional food material. In this study, we sought to examine the anti-atopic effects of 7,3′,4′-trihydroxyisoflavone, an analog of daidzein. Topical application of 7,3′,4′-trihydroxyisoflavone reduced Dermatophagoides farina extract-induced atopic dermatitis symptoms in NC/Nga mice. Histological analysis demonstrated that 7,3′,4′-trihydroxyisoflavone suppressed D. farina extract-induced infiltration of eosinophils and mast cells into skin lesions. We also found that 7,3′,4′-trihydroxyisoflavone significantly reduces the D. farina extract-induced increases in serum IgE and macrophage-derived chemokine (CCL22) levels. We observed that 7,3′,4′-trihydroxyisoflavone suppresses atopic markers including macrophage-derived chemokine (CCL22) and thymus and activation-regulated chemokine (CCL17) in HaCaT cells. 7,3′,4′-Trihydroxyisoflavone also reduced TNF-α/IFN-γ-induced phosphorylation of ERK1/2 and JNK1/2. These results highlight several desirable properties of 7,3′,4′-trihydroxyisoflavone, which support its use as a cosmeceutical ingredient for the treatment of atopic dermatitis.
Keywords: soybean; 7,3′,4′-trihydroxyisoflavone; atopic dermatitis; topical application